Acute Hepatitis E–Associated Acute Pancreatitis: A Single Center Experience and Literature Review. Issue 8 (November 2015) - Raj, Mithun; Kumar, Kundan; Ghoshal, Uday C.; Saraswat, Vivek A.; Aggarwal, Rakesh; Mohindra, Samir
Abstract : Objective: Because acute pancreatitis (AP) associated with acute hepatitis E is rarely reported, we present such a case series. Methods: Records of patients admitted with AP to our institution between May 2007 and December 2013 were reviewed. Diagnosis of AP and acute hepatitis E was based on high serum amylase and/or lipase (>3 times the upper normal limit) and abdominal imaging and presence of serum IgM antibodies against hepatitis E virus, respectively. Other causes of AP were excluded by appropriate evaluation. Results: Of 790 patients with AP, 16 (2.1%; median [range] age, 25 [16–54] years; 15 males) had hepatitis E and no other cause of AP; coexistent hepatitis A and B were present in two and one of them, respectively. Acute pancreatitis began (median [range], 8 [0–35] days) after acute hepatitis and was mild in 10 and severe in 6. Complications included intra-abdominal collections (5), acute renal failure (4), and acute lung injury (2). Median (range) bilirubin, alanine aminotransferase, and prothrombin time were 9.8 (0.4–25) mg/dL, 822 (54–4009) IU/L, 14.6 (9.7–27.4) seconds, respectively. Acute liver failure occurred in 1 patient only. No patient needed surgical, endoscopic, or percutaneous intervention. Conclusions: Acute pancreatitis associated with hepatitis E is not uncommon and usually has good prognosis.